2023
DOI: 10.33988/auvfd.974221
|View full text |Cite
|
Sign up to set email alerts
|

Pathological and molecular findings of visceral gout caused by Israel variant 2 (IS/1494/06) genotype of infectious bronchitis virus in chickens

Abstract: The aim of this study was to investigate pathological lesions and the presence of of Israel variant 2 (IS /1494/06) genotype of infectious bronchitis virus (IBV) in chickens with visceral gout. Sudden deaths were observed in broiler breeders and layer hens belonging to two different flocks located in eastern Turkey. Broiler chickens were previously vaccinated with a vaccine containing strains of IBV Massachusetts serotype, but no information was available about the vaccination history of laying hens. At necrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Monitoring of IB in this study was carried out on breeder, broiler, and layer chickens. As reported before, IBV can infect various types of commercial chickens with various clinical manifestations (Bande et al 2016;Lounas et al 2018;Amarasinghe et al 2018;Wibowo et al 2019;Hassan et al 2022;Timurkaan et al 2021). In this study, we found reproductive symptoms (drop production and cystic oviduct), kidney urate deposits, and respiratory symptoms caused by QX-like strains.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Monitoring of IB in this study was carried out on breeder, broiler, and layer chickens. As reported before, IBV can infect various types of commercial chickens with various clinical manifestations (Bande et al 2016;Lounas et al 2018;Amarasinghe et al 2018;Wibowo et al 2019;Hassan et al 2022;Timurkaan et al 2021). In this study, we found reproductive symptoms (drop production and cystic oviduct), kidney urate deposits, and respiratory symptoms caused by QX-like strains.…”
Section: Discussionsupporting
confidence: 75%
“…Shell-less syndrome (SES) eggs associated with the Massachusetts (Mass) strain of IBV infection (Amarasinghe et al 2018), 4/91-like, and QX-like (Wibowo et al 2019) are another clinical manifestation of the reproductive tract. Timurkaan et al (2021) reported that cases of nephritis and visceral gout were clinical manifestations of the urinary system caused by the Variant 2 strain. The persistence of Australian T and Mass IBV strains has been reported to occur in the caecal tonsils for several months after infection (Najimudeen et al 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation